Pengaruh Level Imbuhan Khamir (Saccharomyces cerevisiae) dalam Pakan Pellet Terhadap Profil Darah Sapi Bali Penggemukan yang Mengonsumsi Pakan Basal Lamtoro - Fallo, Betry Diani; Rosnah, Upik S.; Sobang, Yohanis Umbu Laiya (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to determine the effect of yeast level affixes (Saccharomyces cerevisia) on the blood profile of fattening Bali cows. The cattle used were 12 Balinese cattle in the age range of 2-2.5 years, with a body weight of 156.65 - 218.85kg (x̄ 180.244 kg and KV 12%). This study used a Complete Randomized Design with 4 treatments and 3 repeats. The treatment in this study R0: Lamtoro + Pellet Feed Supplementation 1% BB, R1 : Lamtoro + Pellet Feed Supplementation 1% BB + yeast affix 1g, R2: Lamtoro + Pellet Feed Supplementation 1% BB + Yeast affix 2g, R3: Lamtoro + Pellet Feed Supplementation 1% BB + yeast affix 3g. The data obtained were analyzed using fingerprint analysis (Anova) showing an intangible effect treatment (P>0.05) on the blood profile of fattening Bali cattle. From the results of the discussion, it was concluded that fattening Bali cattle that consumed S. cerevisiae yeasts up to 3g in pelleted feed with lamtoro basal feed showed Hematocrit, Erythrocyte and Leukocyte values were within the normal range.